Parenting styles and internet addiction in college students: self-esteem and self-control as mediators - Gui, Hongyu; Zhao, Qun; Mao, Yuchen (Frontiers in Psychology, 2025)
ObjectivesThis study aimed to explore the effect of parental rearing styles on internet addiction among college students, specifically assessing the mediating roles of self-esteem and self-control in the influencing path.MethodsA cross-sectional questionnaire survey was conducted among college students in a city in eastern China in 2022. Chained mediation effect tests, employing Model 6 of PROCESS with SPSS (27.0), were utilized to statistically analyze the pathways of factors such as parenting styles, self-esteem, and self-control that influence Internet addiction.ResultsPositive parenting styles served as protective factors against internet addiction, whereas negative parenting styles constituted potential risk factors. Self-esteem and self-control fully mediated the association between positive parenting styles and internet addiction. Conversely, they partially mediated the relationship between negative parenting styles and internet addiction.ConclusionInterventions should attach importance to improving positive parenting styles and reducing negative parenting styles, and aim to cultivate self-esteem and strengthen self-control, which are essential to effectively address internet addiction in college students.